2015
DOI: 10.1186/s12888-015-0465-2
|View full text |Cite
|
Sign up to set email alerts
|

Protocol for CHANGE: a randomized clinical trial assessing lifestyle coaching plus care coordination versus care coordination alone versus treatment as usual to reduce risks of cardiovascular disease in adults with schizophrenia and abdominal obesity

Abstract: BackgroundLife expectancy in patients with schizophrenia is reduced by 20 years for males and 15 years for females compared to the general population. About 60% of the excess mortality is due to physical illnesses, with cardiovascular disease being the single largest cause of death.Methods/designThe CHANGE trial is an investigator-initiated, independently funded, randomized, parallel-group, superiority, multi-centre trial with blinded outcome assessment. 450 patients aged 18 years or above, diagnosed with schi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 76 publications
3
16
0
Order By: Relevance
“…Patients were recruited from well‐defined catchment areas in two major Danish cities (Aarhus and Copenhagen). The trial protocol was published in 2015 with no changes made to the original version.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients were recruited from well‐defined catchment areas in two major Danish cities (Aarhus and Copenhagen). The trial protocol was published in 2015 with no changes made to the original version.…”
Section: Methodsmentioning
confidence: 99%
“…These methods were incorporated into four manuals with detailed descriptions of the interventions addressing four tracks: care coordination, smoking cessation, healthy diet, and physical activity. Manuals are provided in the paper describing the trial protocol.…”
Section: Methodsmentioning
confidence: 99%
“…The hypothesis was that a 12-months individually tailored lifestyle coaching intervention would reduce the estimated 10-year cardiovascular-disease risk of, and that the effects would be sustainable with positive results remaining at two-years follow-up. The trial design and the one-year results are described elsewhere[ 8 ], [ 9 ], and showed no effect of the intervention compared with treatment as usual on any outcomes. Based on our theoretical framework Motivational Interviewing and Stages of Change, participants might theoretically have moved from lower towards higher levels of motivation to change health behaviour, resulting in post-intervention weight loss, smoking cessation, improved cardiorespiratory fitness etc.…”
Section: Introductionmentioning
confidence: 99%
“…As part of the CHANGE project [87], peripheral blood (10 mL) and saliva (2 mL) samples were collected in EDTA tubes (BD, Franklin Lakes, NJ, USA) and Oragene saliva collection tubes for DNA extraction (OG-500, DNA Genotek, Ottawa, ON, Canada), respectively, from adult individuals. Blood samples were stored <6 months at −20 • C and saliva samples 6-12 months at ambient temperatures before extraction.…”
Section: Biological Samplesmentioning
confidence: 99%